(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The digital transformation of State-Owned Assets (BMN) management has emerged as a strategic imperative for government institutions to address demands for accountability, transparency, and bureaucratic efficiency. This study analyzes the implementation of the State Asset Management Information System (SIMAN) in the Planning Bureau of the Indonesian Attorney General’s Office (Kejaksaan Agung RI), serving as a case study to evaluate the effectiveness of digital governance in asset management under Minister of Finance Regulation (PMK) No. 118/2023. Employing a descriptive qualitative approach, the research focuses on three pillars of digital governance strategy, policy, and digital standards as a theoretical framework to identify gaps between system design and implementation realities. Findings reveal that while SIMAN is designed as a centralized platform for real-time asset data consolidation, its integration at the Attorney General’s Office faces multidimensional challenges. First, the diversity of BMN (movable/immovable) and their wide geographic distribution complicate data harmonization, particularly in remote regions with limited digital infrastructure. Second, non-technical factors such as employee resistance to systemic changes, reliance on manual procedures (e.g., wet signatures), and insufficiently adaptive work culture emerge as critical barriers. These findings align with the 2023 Supreme Audit Agency (BPK) report, which confirms that 68% of SIMAN implementation obstacles in government institutions are non-technical. The study underscores the necessity of a holistic approach to digital governance, where technological aspects must be balanced with organizational alignment, human resource competency development, and business process transformation. Policy recommendations include enhancing employee capacity through case-based training, revising standard operating procedures (SOPs) to integrate digital-physical hybrid systems, and optimizing supportive infrastructure in underserved regions. Theoretically, this research enriches academic discourse on public sector digitalization by emphasizing the balance between technological innovation and socio-cultural adaptation within Indonesia’s bureaucratic context.